Modeling model selection in model pluralism. Issue 3 (3rd July 2018) - Grüne-Yanoff, Till; Marchionni, Caterina
ABSTRACT: In his recent book, Rodrik [(2015). Economics rules. Why economics works, when it fails, and how to tell the difference . Oxford University Press] proposes an account of model pluralism according to which multiple models of the same target are acceptable as long as one model is more useful for one purpose and another is more useful for another purpose. How, then, is the right model for the purpose selected? Rodrik roughly outlines a selection procedure, which we formalize to enhance understanding of his account of model pluralism and to advance the critical discussion.